'Pandemic drawings': Are we still teaching conceptual drawing?. Issue 2 (1st December 2021) - Borde, Andréa de Lacerda Pessôa; Pessoa, Alexandre
In this paper we analyse the impact of the COVID-19 measures on teaching the conceptual drawing course at the Architecture and Urbanism Faculty of the Federal University of Rio de Janeiro (FAU/UFRJ). The remote model of teaching followed from July 2020 determined many changes in our methodology, these being essentially practical rather than theoretical. This adaptive process resulted in what we called 'pandemic drawings', proved to be a useful tool for expanding drawing skills and confined senses. The outcomes were surprisingly positive and pointed out that these 'pandemic drawings' could become a hybrid model of drawing in the following post-pandemic years.